Kick-ass: the dave lizewski years, book 2 ebook The dave lizewski years vol. 2. - Millar, Mark (Kick-Ass (2008), 2018)
This month marks 10 YEARS OF KICK-ASS.the greatest superhero comic of all time! That also means it's been 10 years since Hit-Girl, the world's deadliest tween assassin, exploded onto the scene to slaughter super villains and serve hot justice to the scum of New York City. In KICK-ASS: THE DAVE LIZEWSKI YEARS, VOL. 2, she trains a novice Kick-Ass in the lethal fighting styles she learned from Big Daddy. In return, Kick-Ass is helping her survive middle school...without any bloodshed. When Kick-Ass gets benched, Hit-Girl has to take on the mafia solo. Collects HIT-GIRL #1-5. Author: Mark Millar. Illustrator: John Romita Jr. . 2018 Dave and Eggsy Ltd. and John S Romita.